Queering the City: Understanding Gravitational Forces - Petra L. Doan (Transatlantica)
This paper uses examples drawn from US cities (Midtown in Atlanta, Georgia, and Ybor City in Tampa, Florida) to develop a more generalizable framework within which to analyze the process of queering a neighborhood and identifying policy measures that might keep it queer. This kind of comparative approach enables a more careful reading of queer urban spaces based on the behaviors of LGBTQ people in and around those spaces. The strategic aim of these comparisons is to expand our understanding of queer spaces and to elaborate a more fluid model of queering cities. The paper uses a gravitational framework that identifies the centering (centripetal) and decentering (centrifugal) forces and the interplay between these forces. Each case provides different lessons for planners regarding the importance of either mitigating or exacerbating the centrifugal tendencies that so often threaten queer spaces. Because these forces are unique to each LGBTQ space, the analytic strategy provides for greater generalizability across different sizes of cities, across various cultural and ethnic areas, and a wider array of geographies.